Интенсификция учебного процесса по иностранному языку в ведомственном вузе с использованием инновационных методик обучения: Portfolio, WebQwest - Талкибаев, А.Б. (My University, 2016)
Modern technologies and methods of teaching foreign language in departmental university. The material of the article is devoted to the modern methods of teaching languages. The article carries material about the advantages and perspectives of using of described technologies in the process of learning in Higher Educational Institutes. These technologies may be considered as the alternative means of evaluation of listeners’ results in their academic activities and personal development
Keywords: technology; method; Portfolio; Case-study; WebQuest; process of learning; listeners; departmental university